The accuracy of biochemical interactions is ensured by endothermic stepwise kinetics. Issue 1 (May 2016) - Michel, Denis; Boutin, Benjamin; Ruelle, Philippe
Abstract: The discerning behavior of living systems relies on accurate interactions selected from the lot of molecular collisions occurring in the cell. To ensure the reliability of interactions, binding partners are classically envisioned as finely preadapted molecules, selected on the basis of their affinity in one-step associations. But the counterselection of inappropriate interactions can in fact be much more efficiently obtained through difficult multi-step adjustment, whose final high energy state is locked by a fluctuation ratchet. The progressive addition of molecular bonds during stereo-adjustment can be modeled as a predominantly backward random walk whose first arrival is frozen by a micro-irreversible transition. A new criterion of ligand specificity is presented, that is based on the ratio rejection/incorporation. In addition to its role in the selectivity of interactions, this generic recipe can underlie other important biological phenomena such as the regular synthesis at low level of supramolecular complexes, monostable kinetic bimodality, substrate concentration thresholds or the preparation of rapidly depolymerizable structures with stored energy, like microtubules.